2022
DOI: 10.3390/electronics11060846
|View full text |Cite
|
Sign up to set email alerts
|

A Feature-Based Approach for Sentiment Quantification Using Machine Learning

Abstract: Sentiment analysis has been one of the most active research areas in the past decade due to its vast applications. Sentiment quantification, a new research problem in this field, extends sentiment analysis from individual documents to an aggregated collection of documents. Sentiment analysis has been widely researched, but sentiment quantification has drawn less attention despite offering a greater potential to enhance current business intelligence systems. In this research, to perform sentiment quantification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Algorithm adaptation approaches modify existing machine learning techniques to handle multilabel classification issues, compared to problem conversion methods, which function as covers over normal machine learning strategies. This work uses BRkNN, a hybrid approach that combines procedures from KNN to and ML [ 35 , 36 ]. The maximal probability concept is used to the study of MLkNN, as suggested in [ 37 , 41 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Algorithm adaptation approaches modify existing machine learning techniques to handle multilabel classification issues, compared to problem conversion methods, which function as covers over normal machine learning strategies. This work uses BRkNN, a hybrid approach that combines procedures from KNN to and ML [ 35 , 36 ]. The maximal probability concept is used to the study of MLkNN, as suggested in [ 37 , 41 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The economic impact of tourism has been examined from several angles in a huge number of research projects. According to the author in [10], long-term economic prosperity may best be achieved through tourism; hence, finding the linkage between tourism and economy can give light to many other factors that connect tourism to economic development. It is evident in todays' society that the tourism industry is evolving quickly.…”
Section: Related Workmentioning
confidence: 99%